Adjuvant Chemotherapy For FIGO Stage IIA2 Cervical Cancer : A Case Report - Heryanto, Deni; Syamel Muhammad; Puja Agung Antonius (Andalas Obstetrics And Gynecology Journal, 2024)
Background : Cervical cancer ranked as the third most prevalent cancer among women. This case report is to examine the current status of adjuvant chemotherapy in the treatment of early-stage cervical cancer as documented in the literature. Currently, there is no established evidence supporting the therapeutic efficacy of adjuvant chemotherapy as a standalone treatment following radical hysterectomy surgery. Nevertheless, some literature recommend the use of adjuvant radiotherapy (AR), adjuvant chemotherapy (AC), or concomitant chemoradiotherapy (CCRT) as the standard adjuvant therapies for early-stage cervical cancer following radical hysterectomy with positive prognostic factor. Case report: A 53-year-old female was diagnosed with stage IIA2 in April 2021. The histology type was determined to be keratinized squamous cell carcinoma, moderately well differentiated. The patient underwent a radical hysterectomy, resulting in the acquisition of uterine and cervical tissue measuring 11x11×6 cm. The histology results revealed moderately to poorly differentiated keratinizing squamous cell carcinoma, with no invasion of the parametrium or pelvic lymph nodes with vaginal cutting margin is free of tumor growth, but lymph vascular space invasion was present. Subsequently, adjuvant chemotherapy was administered using carboplatin (AUC 5) and paclitaxel for a total of 6 cycles. After 2 years with follow-up with CT-Scan examination in April 2023 confirmed the absence of any residual mass. Conclusion: A radical hysterectomy combined with adjuvant chemotherapy has been shown to reduce the chance of recurrence or progressiveness of the disease, in which this patient did not experience a recurrence after two years of treatment